2012
DOI: 10.1074/jbc.m111.320416
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation Product 4-Hydroxy-trans-2-nonenal Causes Endothelial Activation by Inducing Endoplasmic Reticulum Stress

Abstract: Background: Oxidized lipids cause endothelial activation. Results: Endothelial activation by the lipid peroxidation product, 4-hydroxy-trans-2-nonenal, was associated with ER stress and was prevented by chaperones of protein folding. Conclusion: ER stress regulates endothelial activation by oxidized lipids. Significance: Vascular inflammation caused by oxidized lipids could be attenuated by decreasing ER stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 38 publications
6
91
1
Order By: Relevance
“…Studies investigating HNE-mediated changes in LKB1 signaling used an HNE concentration of 40 M (21), which resulted in significant degradation of the LKB1 protein within 1 h. Pathophysiological responses to HNE treatment in cardiac myocytes with concentrations as high as 400 M have been reported to include calcium overload and reactive oxygen species generation (36). HNE has been shown to stimulate autophagy (37) and ubiquitin-mediated proteasomal degradation of proteins (38,39) and to elicit an endoplasmic reticulum stress response in cultured vascular smooth muscle cells (40). By using a relatively low concentration of HNE, our findings are less likely to be confounded by cellular events that may be activated with higher concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating HNE-mediated changes in LKB1 signaling used an HNE concentration of 40 M (21), which resulted in significant degradation of the LKB1 protein within 1 h. Pathophysiological responses to HNE treatment in cardiac myocytes with concentrations as high as 400 M have been reported to include calcium overload and reactive oxygen species generation (36). HNE has been shown to stimulate autophagy (37) and ubiquitin-mediated proteasomal degradation of proteins (38,39) and to elicit an endoplasmic reticulum stress response in cultured vascular smooth muscle cells (40). By using a relatively low concentration of HNE, our findings are less likely to be confounded by cellular events that may be activated with higher concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…HNE was described as inducing ER stress and an UPR in human endothelial cells that had HNE-adducts with proteins colocalizing with ER. 109 These adducted proteins directly affect ER function, especially protein disulfide isomerase. 110 In support of this idea, it was shown that the folding of protein to allow optimal formation of disulfide bonds is highly redox-dependent in the ER.…”
Section: Hne: a Serial Killermentioning
confidence: 99%
“…The gel pieces were then washed twice with water and cut in half. One half of the band was digested with 60 ng of trypsin (Promega) as described previously (35); the other half of each band was digested with 60 ng of Arg-C (Sigma) in 50 mM triethylammonium bicarbonate. After digestion, peptides were sequentially extracted from the gel pieces using 5% v/v formic acid and acetonitrile (36).…”
mentioning
confidence: 99%